Biofilm adaptation to iron availability in the presence of biotite and consequences for chemical weathering. Issue 6 (6th July 2016) - Grant, M. R.; Tymon, L. S.; Helms, G. L.; Thomashow, L. S.; Kent Keller, C.; Harsh, J. B.
Abstract: Bacteria in nature often live within biofilms, exopolymeric matrices that provide a favorable environment that can differ markedly from their surroundings. Biofilms have been found growing on mineral surfaces and are expected to play a role in weathering those surfaces, but a clear understanding of how environmental factors, such as trace‐nutrient limitation, influence this role is lacking. Here, we examine biofilm development by Pseudomonas putida in media either deficient or sufficient in Fe during growth on biotite, an Fe rich mineral, or on glass. We hypothesized that the bacteria would respond to Fe deficiency by enhancing biotite dissolution and by the formation of binding sites to inhibit Fe leaching from the system. Glass coupons acted as a no‐Fe control to investigate whether biofilm response depended on the presence of Fe in the supporting solid. Biofilms grown on biotite, as compared to glass, had significantly greater biofilm biomass, specific numbers of viable cells (SNVC), and biofilm cation concentrations of K, Mg, and Fe, and these differences were greater when Fe was deficient in the medium. Scanning electron microscopy (SEM) confirmed that biofilm growth altered the biotite surface, smoothing the rough, jagged edges of channels scratched by hand on the biotite, and dissolving away small, easy‐to‐access particles scattered across the planar surface. High‐resolution magic angle spinning proton nuclear magnetic resonance (HRMAS 1 H NMR) spectroscopy showed that, in the Fe‐deficient medium, the relative amount of polysaccharide nearly doubled relative to that in biofilms grown in the medium amended with Fe. The results imply that the bacteria responded to the Fe deficiency by obtaining Fe from biotite and used the biofilm matrix to enhance weathering and as a sink for released cation nutrients. These results demonstrate one mechanism by which biofilms may help soil microbes overcome nutrient deficiencies in oligotrophic systems.